Immoral behaviour following brain damage: A review. Issue 3 (16th April 2018) - Roberts, Stefanie; Henry, Julie D.; Molenberghs, Pascal
Abstract : Despite the apparent sociability of human kind, immoral behaviour is ever present in society. The term 'immoral behaviour' represents a complex array of conduct, ranging from insensitivity to topics of conversation through to violent assault and murder. To better understand the neuroscience of immoral behaviour, this review investigates two clinical populations that commonly present with changes in moral behaviour – behavioural‐variant frontotemporal dementia and acquired brain injuries. Based on evidence from these groups, it is argued that rather than a single underlying cause, immoral behaviour can result from three distinct types of cognitive failure: (1) problems understanding others; (2) difficulties controlling behaviour; or (3) deficits in the capacity to make appropriate emotional contributions . Each of these failures is associated with damage to different brain regions. A more nuanced approach to the neuroscience of immoral behaviour has important implications for our understanding of immoral behaviour in a wide range of clinical groups, as well as human society more broadly.